When a clonal genome finds its way back to a sexual species: evidence from ongoing but rare introgression in the hybridogenetic water frog complex. (7th February 2014) - Mikulíček, P.; Kautman, M.; Demovič, B.; Janko, K.
Abstract Besides several exceptions, asexual metazoans are usually viewed as ephemeral sinks for genomes, which become 'frozen' in clonal lineages after their emergence from ancestral sexual species. Here, we investigated whether and at what rate the asexuals are able to introgress their genomes back into the parental sexual population, thus more or less importantly affecting the gene pools of sexual species. We focused on hybridogenetic hybrids of western Palaearctic water frogs (Pelophylax esculentus), which originate through hybridization between P. ridibundus and P. lessonae, but transmit only clonal ridibundus genome into their gametes. Although usually mating with P. lessonae, P. esculentus may upon mating with P. ridibundus or another hybrid produce sexually reproducing P. ridibundus offspring with the introgressed ex‐clonal genome. We compared the rate of nuclear amplified fragment length polymorphism (AFLP) and mitochondrial introgression in two types of populations, that is, those where P. ridibundus occurs in isolation and those where it lives with the hybridogens. Although significant differentiation (Φpt) between sexual and clonal ridibundus genomes suggested limited gene flow between sexuals and hybridogens, a non‐negligible (~5%) proportion of P. ridibundus bore introgressed mtDNA and AFLP markers. Whereas transfer of mtDNA was exclusively unidirectional, introgression of nuclear markers was bidirectional. The proportion of introgressed P. ridibundus was highest in syntopic populations with P. esculentus, proving an ongoing and site‐specific interspecific genetic transfer mediated by hybridogenetic hybrids. It turns out that asexual hybrids are not just a sink for genes of sexual species, but may significantly influence the genetic architecture of their sexual counterparts.